Venture capital contracting under asymmetric information - Trester, Jeffrey J. (Journal of Banking & Finance, 1998)
A model is developed wherein entrepreneurs and venture capitalists contract under symmetric information. Asymmetric information may arise following first contracting. It is shown this can lead to debt infeasibility and preferred equity usage. Control is linked to choice between common and preferred. Results are robust to multiperiod extensions. Roles of convertible preferred, retained equity, and debt in IPOs are considered. An empirical survey of venture capital firms is presented demonstrating preferred dominates in early financing. Debt and common are used far less – generally at later stages under lower probability of asymmetric information. These results agree with the theory's implications.